Edwards K.: The English Secular Cathedrals in the Middle Ages - Roman, Stanisław (Czasopismo Prawno-Historyczne, 1951)
Recenzja: Edwards Kathleen: The English Secular Cathedrals in the Middle Ages — A Constitutional Study with Special Reference to the Fourteenth Century, Publications of the University of Manchester No. CCCI, Historical Series No LXXXII, Manchester University Press 1949, str. XV+ 415 + 4 ilustracje